Pengaruh Aplikasi E-Office Terhadap Peningkatan Kinerja Pegawai Pada Kantor Walikota Jakarta Barat Tahun 2022 - Zakiyah Fitri; Tulus Santoso (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
In order to guarantee the provision of accurate, open, centralized and integrated data and information services, it is necessary to regulate the guidelines for the collection and exchange of electronic data within the Provincial Government of the Special Capital City Region of Jakarta with Governor Regulation no. 06 of 2020 and Governor's Instruction No. 64 of 2021 regarding the acceleration of the use of E-Office. One example of the application of information technology in the DKI Jakarta Provincial Government is the development of E-Office applications. This study aims to determine the effect of using E-Office applications on employee performance. This study also limits the scope, namely only City Secretariat employees at the West Jakarta Mayor's office in 2022. The type of research used in this study is quantitative research with a descriptive approach. The results of the study stated that there was an influence between E-Office on employee performance for employees at the West Jakarta Mayor's Office of 70.8%. While 19.8% outside the variables that the authors examine.